Pathophysiology and clinical aspects of epiretinal membrane – review - Ożóg, Mateusz Kamil; Nowak-Wąs, Marta; Rokicki, Wojciech (Frontiers in Medicine, 2023)
The epiretinal membrane (ERM) is a pathological tissue formed at the vitreoretinal interface. The formation of this tissue is associated with numerous symptoms related to disturbances of vision. These types of lesions may arise idiopathically or be secondary to eye diseases, injuries and retinal surgeries. ERM tissue contains numerous cell types and numerous cytokines, which participate in its formation. The aim of this paper is to summarize information about the etiology, epidemiology, pathophysiology and treatment of ERM, with a brief description of the main cells that build the ERM – as well as the cytokines and molecules related to ERM pathogenesis – being provided in addition.